ANALYSIS OF THE QUALITY OF ANTENATAL CARE (ANC) SERVICES AND USG SERVICE FACILITIES ON PATIENT SATISFACTION THROUGH THE COMPETENCE OF HEALTH WORKERS (STUDY ON PREGNANT WOMEN IN JEMBER DISTRICT) - Ahmad, Sri Isna Amelia (Proceeding of International Conference on Social Science and Humanity, 2025)
Objective: To analyze the influence of antenatal care and service facility (ultrasound/ultrasound) service quality on patient satisfaction by considering the role of health workers' competence as a mediating variable in pregnant women in the Jember Regency Health Center area. Method: This study uses a quantitative approach with descriptive and analytical design. This approach was used to describe the condition of antenatal care service quality, service facilities (ultrasound/ultrasound). Results: Patient satisfaction with ANC services is influenced by various factors, such as service quality, service facilities (ultrasound/ultrasound), and the competence of health workers. Novelty: This study considers the role of health worker competence as an intervening variable in the relationship between antenatal care service quality, service facilities (ultrasound/ultrasound), and patient satisfaction in pregnant women in the Jember Regency Health Center area.